Komodifikasi Dakwah Melalui Media Sosial Instagram - Melyna Mazlin, Rosa; Fikri Zuhriyah, Luluk; Syam, Nur; Hanifah, Najmy (Idarotuna, 2025)
The development of digital technology has transformed various aspects of life, including how people communicate and disseminate religious values. Generation Z, as digital natives, plays a central role in utilizing social media, including accessing Islamic preaching (dakwah) content. This study focuses on the Instagram account @ayah_amanah, which features the Sharing Time dakwah program led by Ustadz Hanan Attaki. The purpose of this research is to analyze the commodification process of dakwah through Instagram and to examine how audience interaction occurs within the framework of social exchange. Using a qualitative approach with critical discourse analysis, the study integrates Karl Marx’s theory of commodification and the social exchange theories of George C. Homans and Peter M. Blau. The findings aim to demonstrate that digital dakwah is not merely a means of spiritual communication but also a commodified product packaged, distributed, and consumed within the social media ecosystem. This research also reveals how visuals, narratives, and branding strategies shape power relations and meanings in the dissemination of contemporary Islamic messages. The study offers a new contribution by bridging digital dakwah in the context of Instagram.